1991
DOI: 10.2135/cropsci1991.0011183x003100040023x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Full‐Sib Recurent Selection in Maize: I. Direct and Indirect Responses

Abstract: Interpopulation recurrent selection methods can be used for developing new heterotic patterns and enhancing those identified previously. The objective of this research was to estimate the direct and indirect responses to eight cycles of reciprocal full‐sib recurrent selection in maize (Zea mays L.) populations BS10 and BS11. The populations and their crosses corresponding to Cycles 0, 2, 4,6, and 8 were evaluated at two levels of inbreeding (F = 0 and F = 0.5), and populations also were testcrossed to the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
3
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 0 publications
9
40
3
3
Order By: Relevance
“…Trabalhos com populações derivadas de híbridos simples mostraram respostas de 5,7 (Raposo et al, 2004), 4,5 e 6,2% (Coors, 1999) à seleção por ciclo. Em programas com populações temperadas (BS10 e BS11) submetidas à SRR de irmãos germanos por oito ciclos, Eyherabide & Hallauer (1991) reportaram ganho de 6,5% por ciclo. Keeratinijakal & Lamkey (1993), ao trabalhar com as populações BSSS e BSBC1 por 11 ciclos, relataram ganho de 6,95% com a seleção por ciclo.…”
Section: Methodsunclassified
“…Trabalhos com populações derivadas de híbridos simples mostraram respostas de 5,7 (Raposo et al, 2004), 4,5 e 6,2% (Coors, 1999) à seleção por ciclo. Em programas com populações temperadas (BS10 e BS11) submetidas à SRR de irmãos germanos por oito ciclos, Eyherabide & Hallauer (1991) reportaram ganho de 6,5% por ciclo. Keeratinijakal & Lamkey (1993), ao trabalhar com as populações BSSS e BSBC1 por 11 ciclos, relataram ganho de 6,95% com a seleção por ciclo.…”
Section: Methodsunclassified
“…O esquema de famílias deste delineamento, freqüentemente utilizado na cultura do milho (Hallauer & Miranda Filho, 1988;Eyherabide & Hallauer, 1991;Furtado, 1996), permite adotar diferentes estraté-gias de seleção, tais como: seleção entre machos, fê-meas, fêmeas hierarquizadas a machos e seleção combinada (Cruz & Carneiro, 2003).…”
Section: Introductionunclassified
“…One cycle of the modified (MRRS) procedure designed by Rezende and Souza Jr. (2000) increased grain yield by 16.7% and reduced significantly plant and ear heights. In a per cycle basis, this MRRS procedure increased grain yield at a higher rate than the 6.0% to 7.0% reported for standard RRS programs where 10% to 20% as selection intensity and S 1 lines for recombination were used (Eyherabide and Hallauer, 1991;Santos et al, 2007;Santos et al, 2005;Souza Jr. and Pinto, 2000). Then, the MRRS procedure was highly effective in improving the population cross performance in only one cycle of selection.…”
Section: Introductionmentioning
confidence: 75%
“…Reciprocal recurrent selection (RRS) is a long-term cyclical breeding procedure outlined to improve population crosses, and reported results have shown that RRS has been very effective (Eyherabide and Hallauer, 1991;Souza Jr. and Pinto, 2000;Santos et al, 2005), and also the improved populations have been sources of elite inbreds and outstanding single-crosses Betrán and Hallauer, 1996). The elite inbred lines from the RRS programs are unrelated to the inbreds developed from the recycling programs, and then they could be incorporated to these programs to maintain the rate of the development and release of new hybrids.…”
Section: Introductionmentioning
confidence: 99%